2016
DOI: 10.1021/acs.jpcc.6b06197
|View full text |Cite
|
Sign up to set email alerts
|

Atom Probe Tomography Analysis of Boron and/or Phosphorus Distribution in Doped Silicon Nanocrystals

Abstract: Silicon nanocrystals (Si NCs) are intensively studied for optoelectronic and biological applications due to having highly attractive features such as band engineering. Although doping is often used to control the optical and electrical properties, the related structural properties of solely doped and codoped Si NCs are not well-understood. In this study, we report the boron (B) and/or phosphorus (P) distribution in Si NCs embedded in borosilicate glass (BSG), phosphosilicate glass (PSG), and borophosphosilicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
82
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 50 publications
15
82
2
Order By: Relevance
“…In these cases the formation energy assumes negative values. It is interesting to note that Nomoto et al [129] have observed that codoping is an effective means of promoting segregation and stability of the These results are confirmed by the calculation performed in the case of multidoping [235]. In Fig.…”
Section: Codopingsupporting
confidence: 76%
See 2 more Smart Citations
“…In these cases the formation energy assumes negative values. It is interesting to note that Nomoto et al [129] have observed that codoping is an effective means of promoting segregation and stability of the These results are confirmed by the calculation performed in the case of multidoping [235]. In Fig.…”
Section: Codopingsupporting
confidence: 76%
“…However, the self-purification effects can be strongly influenced by the presence of defects, vacancies or different capping species used to saturate the dangling bonds at the interface; this fact explains the efficient incorporation of dopant atoms in small Si-NCs with diameter less than 2 nm [129,153,154,155,156].…”
Section: Ab-initio Calculations: Formation Energies Role Of Sizes Smentioning
confidence: 99%
See 1 more Smart Citation
“…Both, P and B, were found to be distributed nearly equally across both phases. This is in contrast to thermally grown films of Si nanocrystalls embedded in a SiO 2 matrix where an increased P content was found in the Si nanocrystalls for n-type material and a decreasing amount of B towards the inner part of the nanocrystalline Si for p-type material [20]. A possible cause might be a lack of time and/or energy provided to the system during PECVD to rearrange the dopant atoms to their thermodynamically favorite sites.…”
Section: Discussionmentioning
confidence: 70%
“…Before, a 300 nm layer of Pt was deposited on the films to prevent damage from Ga ions during the FIB milling. More details on the sample preparation can be found in [20]. The measurements were performed on a CAMECA LEAP 4000Xsi with a pulsed 355 nm laser (250 kHz, 50 pJ) and an overall detection efficiency of 57 %.…”
Section: Methodsmentioning
confidence: 99%